Pengaruh Tingkat Inflasi Dan Jumlah Wajib Pajak Terhadap Realisasi Penerimaan Pajak Bumi Dan Bangunan Perdesaan Dan Perkotaan (PBB-P2) Pada Kota Bandung Periode 2014-2021 - Nissa Yuniar Nur Alifah; Diana Sari (Journal of Economic, Bussines and Accounting (COSTING), 2023)
The purpose of this study is to estimate changes in land and building tax revenues for the City of Bandung in 2014-2021 by considering the impact of inflation and the number of taxpayers. This information was compiled using records and reports from the Bandung Regional Revenue Management Agency and the Bandung Central Bureau of Statistics (BPS). Information is provided regarding the inflation rate in Bandung City, the number of taxpayers of PBB-P2 in Bandung City, and the income of PBB-P2 in Bandung City. Data collection is carried out every quarter for 8 years, from 2014-2021, in the form of periodic data (time series data). In this study, we used a descriptive verification strategy. Saturated sampling was used, and the resulting sample size was 32 observations. This study used descriptive statistics, multiple linear regression analysis with the help of SPSS 29 software, and classical assumption tests (normality, multicollinearity, heteroscedasticity, and autocorrelation) and hypothesis testing (t test and coefficient of determination). The research results show that the number of taxpayers has a positive and quite large effect on the realization of PBB-P2 revenues, while the inflation rate has no significant effect. Keywords : Inflation rate, Number of taxpayers, and Realization of PBB-P2